Help-seeking behaviors and determinant factors among women exposed to intimate partner violence in East Africa based on recent demographic and health survey data: a multilevel analysis - Melkam, Mamaru; Asnake, Angwach Abrham; Mekuria Negussie, Yohannes; Bezie, Meklit Melaku; Asmare, Zufan Alamrie; Asebe, Hiwot Altaye; Seifu, Beminate Lemma; Fente, Bezawit Melak (Frontiers in Psychiatry, 2024)
Introduction Human rights violations and violence against women are serious public health issues that have numerous detrimental repercussions on one’s physical, emotional, sexual, and reproductive health. According to studies, women’s perceptions and traits of violence are highly predictive of their likelihood of seeking help against violence. Even though intimate partner violence is a huge challenge nowadays in Africa, there is a low level of help-seeking behavior. Conducting this study at the East African level on help-seeking behavior can provide a clue for policy-makers. Therefore, this study aimed to reveal the prevalence of help-seeking behavior against intimate partner violence and determinant factors among women in East Africa. Method Multilevel logistic regression analysis was carried out among East Africans using recent demographic and health survey data. A total of 7,387 participants aged 15 to 49 years were included in this study from East African countries. Individual- and community-level variables were considered to determine the associated factors with help-seeking behaviors against intimate partner violence with 95% CI and AOR. Results The prevalence of help-seeking behavior against intimate partner violence among women was 38.07% with 95% CI (36.96%, 39.18%). Husbands drink alcohol [AOR = 1.46: 95% CI (1.33, 1.61)], women who have work [AOR = 1.33: 95% CI (1.19, 1.50)], and women with higher educational status [AOR = 1.36: 95% CI (1.16, 1.59)] were factors associated with help-seeking behavior against intimate partner violence. Conclusion Approximately four out of 10 women were seeking help for intimate partner violence in East Africa. Husbands drinking alcohol, women’s high educational status, and women having occupations were the factors that were associated with help-seeking behaviors against intimate partner violence.